Status of company law in the Commonwealth Caribbean. - Stanford, Lurline (1990)
Summarises the major reforms proposed in the Report of the Working Party on the Harmonisation of Company Law in the Caribbean Community. Notes that the recommendations may exercise a beneficial influence on subsequent company law reform in the region. Points out that mandatory harmonisation of company law is outside the CARICOM agreement.